Sebastiano Ricci impresario d'opera a Venezia nel primo Settecento - Stefani, Gianluca (Premio Ricerca «Città di Firenze», 2015)
Sebastiano Ricci was not only one of the greatest Italian and international painters of the eighteenth century, but an opera impresario and a set designer. Thanks to unpublished archival documents, this book reconstructs and interprets the phases of his theatrical career, well known in Parma and Rome in 1690 and 1694 and continued with discontinuity in the circuit of public theaters in Venice in the first three decades of the eighteenth century. Through the portrait of the artist impresario, enriched by new biographical data, the author sheds light on the still elusive theatrical and musical world of the time, animated by well-known characters such as the Red Priest Vivaldi, the castrato Cortona, the impresario Orsatto and unknown persons such as the impresario Modotto, the fixer Viola, the violinists Madonis.